Lipids as Triggering Factors in Thrombosis - Nordøy, Arne (Thrombosis and Haemostasis, 1976)
An association has been established between acute and more persistent changes in lipid metabolism as reflected in plasma lipids, and platelet lipid metabolism. Platelet function is affected, particularly the activity and availability of platelet factor 3, however, also other changes making the platelets more sensitive to aggregating substances without interfering with the lipid part of platelet factor 3, have been documented. Experimental studies have demonstrated an increased tendency to thrombosis in animals given a diet with a high fat content with a high ratio of saturated to polyunsaturated fatty acids. Studies in man have mainly established a connection between dietary fats, plasma lipid abnormalities and frequency of coronary heart disease and clinical studies more directly relating thrombosis to lipid metabolism is highly warranted. Many open questions remain to be answered. Probably most relevant would be to understand how the antithrombotic mechanisms in the body are affected by changes in lipid metabolism. Even if thrombotic lesions are very common events in the western world our knowledge based on laboratory and experimental studies should indicate a much higher incidence, solely based on interactions between lipids and platelets in subjects exposed to our dietary habits and our way of life.